Early removal of nasogastric tube with early feeding versus conventional removal of nasogastric tube with delayed feeding after bowel anastomosis: a prospective randomized controlled trial - Negi, Anil; Kumar, Dhiraj; Rajput, Neeraj Singh; Pandey, Avinash; Gawer, Divyansh; Ansari, Afzal Ahmad (International Surgery Journal, 2019)
Background: Nasogastric (NG) decompression and delayed oral feeding after bowel anastomosis is conventional and years old practice. The aim of the present study was to evaluate the advantages and disadvantages of early removal of naso gastric tube (<24 hrs) and delayed feeding, compared with delayed removal and delayed enteral feeding in patients undergoing bowel anastomosis. Methods: It is a single blind, prospective randomized study involving patients with bowel anastomosis from December 2016- November 2018 at a tertiary care hospital. In study group naso gastric tube was removed within 24 hours. After 12 hours of surgery patients were allowed sips of water, then free liquids followed by semisolid and normal diet in calculated way. In control group naso gastric tube was retained till passage of flatus and orally allowed only after passage of stool. Results: A total of 241 patients were enrolled. In study group bowel sound returned after 30.57±31.19 hours of surgery and in control group 46.90±48.65 hours and this difference was significant (p<0.002). In study group first free liquid was allowed on 38.14±38.50 hours in post operative period, as compared to the control group where free liquids were allowed after 50.09±51.80 hours this difference was significant (p<0.04). Total hospital stay in the study group was significant (p<0.02). Conclusions: Early removal of naso gastric tube and early feeding is better than the conventional practice.